Illness perception sebagai supporting factor terhadap treatment motivation pada pasien kanker - Prasetya, Arief Widya; Werdani, Yesiana Dwi Wahyu (Holistik Jurnal Kesehatan, 2025)
Background: Illness perception towards cancer disease varies widely from bad perception to good perception. The perception held by cancer patients can be an important factor in decision making to undergo treatment. Purpose: To explain illness perception as a supporting factor for treatment motivation in cancer patients. Method: A cross-sectional quantitative study was conducted at the Indonesian Cancer Foundation, East Java Branch, Surabaya in January 2022. The sampling technique used purposive sampling with a sample size of 50 respondents. The independent variable in this study is the perception of the disease and the dependent variable is the motivation to seek treatment. Data analysis used univariate in the form of frequency distribution and bivariate using linear regression test. Results: Illness perception has a significant effect on treatment motivation (p < 0.05) with a contribution of 0.588, indicate perception of illness plays an important role as a supporting factor in shaping treatment motivation in cancer patients. Conclusion: Positive Illness perception and family support have an important role in increasing treatment motivation in cancer patients   Keywords: Cancer; Illness Perception; Treatment Motivation   Pendahuluan: Illness perception terhadap penyakit kanker sangat bervariasi,  mulai dari persepsi yang buruk sampai yang baik. Persepsi yang dianut pasien kanker dapat menjadi faktor penting untuk pengambilan keputusan menjalani pengobatan. Tujuan: Untuk menjelaskan illness perception sebagai supporting factor terhadap treatment motivation pada pasien kanker. Metode: Penelitian kuantitatif cross-sectional, dilaksanakan di Yayasan Kanker Indonesia Cabang Jawa Timur Surabaya pada bulan Januari 2022. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah sampel sebanyak 50 responden. Variabel independen dalam penelitian ini adalah illness perception dan variabel dependen adalah treatment motivation. Analisis data yang digunakan univariat dalam bentuk distribusi frekuensi dan bivariat menggunakan uji regresi linear. Hasil: Illness perception memiliki pengaruh yang signifikan terhadap treatment motivation (p < 0.05) dengan kontribusi sebesar 0.588, menunjukkan bahwa persepsi terhadap penyakit berperan penting sebagai faktor pendukung dalam membentuk motivasi pengobatan pada pasien kanker. Simpulan: Illness perception yang positif dan dukungan keluarga berperan penting dalam meningkatkan motivasi pengobatan pada pasien kanker.   Kata Kunci: Illness Perception; Kanker; Treatment Motivation.